Long-term efficacy and ocular surface of pterygium excision combined with autologous corneal limbal stem cell transplantation in treatment of pterygium - WangXiahong; ChenJiling (眼科学报; 卷 30, 编号 3 (September 2015): 《眼科学报》, 2015)
Purpose: To evaluate the long-term efficacy of pterygium excision combined with autologous corneal limbal stem cell transplantation in the treatment of pterygium. Methods: Fifty five patients (57 eyes) diagnosed with primary pterygium undergoing pterygium excision combined with autologous corneal limbal stem cell transplantation between December 2003 and December 2008 were enrolled in this study. Postoperative follow-up endured for 2-8 years, 5.3 years on average. The wound healing, clinical efficacy and postoperative complications were observed. Results: During early stage after surgery, all patients presented with varying degree of hyperemia, edema and sense of foreign body, which were gradually mitigated 3-5 d later and completely recovered in approximately 1 week. The corneal wound was completely epithelized within 4-7 d, 4.83 d on average. Seven patients had persistent ocular surface irritation symptoms after surgery, one case had residual fibrous tissues and four patients developed superficial corneal scars. Postoperative follow-up endured for 2-8 years, 5.3 years on average. Eight patients (8 eyes) recurred with a recurrence rate of 13.11%. In all patients, postoperative OSDI score was significantly decreased at 1-year reexamination. OSDI score and constitution ratio significantly differed between two groups (both P 0.05). At postoperative 1- and 5-year, basic tear secretion was (12.95±4.03) mm and (12.68±4.77) mm, tear film break-up time was (10.55±4.13) s and (10.03±4.64) s. Both indexes were significantly improved compared with (9.48±3.34) mm and (8.14±3.57) s before surgery (all P<0.05). Conclusion: Pterygium excision combined with autologous corneal limbal stem cell transplantation is an efficacious treatment of pterygium with mild postoperative symptoms, rapid recovery, low long-term recurrence rate and high efficacy.